2017
DOI: 10.1364/ao.56.0000e8
|View full text |Cite
|
Sign up to set email alerts
|

Study of propagation of vortex beams in aerosol optical medium

Abstract: A theoretical and experimental study of the propagation of vortex laser beams in a random aerosol medium is presented. The theoretical study is based on the extended Huygens-Fresnel principle with the generation of a random field, using the fast Fourier transform. The simulation shows that the stability of vortex beams to fluctuations of an optical medium falls with rising order of optical vortices. Moreover, a coherence length (radius) of the random medium is of great importance. The coherence radius extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…It can be explained by the fact that, in the second case, two correlation peaks are formed, which leads to a redistribution of the intensity between them and an increase in the fluctuation of the intensity of each correlation peak. However, it should be noted that the value obtained in the case of detection of a single OAM state is much less than the previously obtained value of the scintillation index for the case of OV beams with TCs up to five propagating through the scattering medium and detected without any diffractive multichannel filter [17]. Besides, the value of the scintillation index that is obtained in the case of detection of the superposition of OV beams with different OAM states is comparable to these values.…”
Section: Figurecontrasting
confidence: 58%
See 2 more Smart Citations
“…It can be explained by the fact that, in the second case, two correlation peaks are formed, which leads to a redistribution of the intensity between them and an increase in the fluctuation of the intensity of each correlation peak. However, it should be noted that the value obtained in the case of detection of a single OAM state is much less than the previously obtained value of the scintillation index for the case of OV beams with TCs up to five propagating through the scattering medium and detected without any diffractive multichannel filter [17]. Besides, the value of the scintillation index that is obtained in the case of detection of the superposition of OV beams with different OAM states is comparable to these values.…”
Section: Figurecontrasting
confidence: 58%
“…where m is an integer value of a topological charge (TC). The convenience of OVs lies in the independence of the field radius, which provides versatility [22][23][24]42] and significant tolerances for aligning the optical system [17,18].…”
Section: Development Of Multichannel Filters and Modelling Of The Sorting Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Since laser beams with OAM are of special interest for data channel multiplexing [ 2 , 68 , 69 ]. Many studies are devoted to the propagation of OV beams as in free space [ 70 , 71 , 72 , 73 ] and in optical fibers [ 74 , 75 , 76 ]. To implement multichannel information transfer using OAM, a certain superposition of OVs with a given energy and phase distribution in the transmitter must be excited on the transmitting side, so each mode transmits an independent information signal.…”
Section: Oam Emitters Based On Diffractive Optic Elementsmentioning
confidence: 99%
“…Several reports conjectured that, because they carry OAM, OVs propagate through optical turbulence with less distortion than conventional Gaussian beams 34 36 . Other experimental studies have shown that, in comparison with Gaussian beams, OVs are less stable for small propagation distances but they become more resilient over considerable distances 37 . Indeed, there are different criteria for beam stability.…”
Section: Introductionmentioning
confidence: 96%